KEBERADAAN DAN IMPLIKASI PRINSIP MFN DAN NT DALAM PENGATURAN HAK KEKAYAAN INTELEKTUAL DI INDONESIA - Ni Ketut Supasti Dharmawan (University of Udayana, 2014)
The WTO – TRIPs Agreement regulates the principle of non- discrimination which must be complied by its member countries. There are two principle of non discriminationnamely the principle of National Treatment ( NT ) and Most Favoured Nations principle (MFN). This study focus to the adoption of MFN and NT principles into IntellectualProperty Rights laws of Indonesia whether it harmony with the legal system in Indonesia. This study uses the normative legal research methods by using conceptual approachand statute approach . The legal materials that studies in this research consists of thePrimary Legal Materials : Act No. 19 of 2002 , Act No. No. . 15 of 2001, Act No. 14 of2001, as well as the TRIPs Agreement. Secondary legal materials studied in this research are legal text books and law journals related to NT and MFN principle in the field of IntellectualProperty Rights. .The results showed that the Principle of Non Discrimination System in the form of theprinciple of National Treatment (NT) expressly governed through Article 3 TRIPsAgreement and the principle of Most Favoured Nations (MFN) regulated through Article 4TRIPS Agreement. As a member of WTO-TRIPs Agreement, Indonesia should comply andadopt the MFN and NT principles into IPR laws. Currently those principles exist implicitlyand explicitly such as in the Act No. 19 of 2002, the Act No. 14 of 2001, and the Act No. 15of 2001. Although the MFN and NT principles has already adopted, it is still need moreeffort to implement the principle of non Discrimination, especially in the relationshipbetween Indonesia and other unequal size countries, between developing and developedcountries.